A Cadaver Study to Assess the Feasibility of a Cross-Nerve Transfer of the Infraorbital Nerve for Patients With Peripheral Infraorbital Nerve Injury. Issue 2 (February 2018) - Yano, Tomoyuki; Akita, Keiichi; Yamaguchi, Kumiko; Sawaizumi, Masayuki
Abstract : Background: Patients with facial fracture or head and neck surgery sometimes suffer from infraorbital nerve injury. This injury results in severe hemilateral numbness in the midfacial area. The infraorbital nerve ends with two major branches; the infra nasal branch (INB) and superior labial branch (SLB). In this study, we assessed the feasibility of cross-nerve transfer of the INB and SLB based on a cadaver study. Methods: The INB/SLB from a total 20 sides of 10 cadavers (2 men and 8 women; average age, 79.9 years) were dissected. The distribution patterns of the INB and SLB, the distance between the INB/SLB and the piriform aperture, and the shortest distance between the INB/SLB were estimated. Results: Three distribution patterns of the INB and SLB were observed, that is type A (65%); only the INB is thick enough for a nerve transfer, type B (20%); only the SLB is thick enough for a nerve transfer, and a combination of types A and B (15%). The distance between the INB, SLB and the piriform aperture was on average 8.61 and 10.81 mm in each. The shortest distance between the INB and SLB was on average 11.34 ± 3.7 mm. Conclusions: The INB and SLB existed in all the specimens and could be found approximately 1 cm below the piriform aperture. The average distance between the INB and SLB was approximately 11 mm. These results imply the feasibility of a cross-nerve transfer of the distal part of the infraorbital nerve.